Depth and physical properties of soil in a forest and a rubber plantation in Peninsular Malaysia - Tsuboyama, Y. (2017)
Soil depth and soil physical properties were investigated in a tropical rain forest and a rubber plantation in Peninsular Malaysia. For the forested site, thickness of surface soil layer (A and B horizons) and total soil depth ranged from 52 to 160 cm and from 118 to 640 cm respectively. The corresponding values for riser bank in the rubber plantation ranged from 42 to 121 cm and from 106 to 162 cm respectively. Total soil depth at the terrace bench in the rubber plantation was shallower (mean: 119 cm) than at the riser bank. The saturated hydraulic conductivity (Ks) in the forested site and plantation site ranged from 6.40 x 10-6 to 7.51 x 10-4m s-1 and from 1.79 x 10-6 to 5.68 x 10-4 m s-1 respectively. The Ks values decreased with increasing soil depth at both sites. The average Ks values in the forested site were larger (10cm: 1466 mm h-1, 80 cm: 169 mm h-1) than the prevailing rainfall intensity in this region. Although the average Ks values at the riser bank in the rubber plantation were similar to those in the forested site, the average Ks values at the terrace bench in the rubber plantation were smaller (10 cm: 68 mm h-1, 40 cm: 29 mm h-1). The macro- and mesoporosity of the soil also decreased with increasing soil depth. The soil porosities were in the following order of magnitude: forest > riser bank > terrace bench. These hydrological parameters (soil depth, Ks value and porosity) between the forested and rubber plantation sites enable us to understand the difference of function for water conservation concerning land-use classification.